How Smooth Muscle Contractions Shape the Developing Enteric Nervous System - Chevalier, Nicolas R.; Agbesi, Richard J. Amedzrovi; Ammouche, Yanis; Dufour, Sylvie (Frontiers in Cell and Developmental Biology, 2021)
Neurons and glia of the enteric nervous system (ENS) are constantly subject to mechanical stress stemming from contractions of the gut wall or pressure of the bolus, both in adulthood and during embryonic development. Because it is known that mechanical forces can have long reaching effects on neural growth, we investigate here how contractions of the circular smooth muscle of the gut impact morphogenesis of the developing fetal ENS, in chicken and mouse embryos. We find that the number of enteric ganglia is fixed early in development and that subsequent ENS morphogenesis consists in the anisotropic expansion of a hexagonal honeycomb (chicken) or a square (mouse) lattice, without de-novo ganglion formation. We image the deformations of the ENS during spontaneous myogenic motility and show that circular smooth muscle contractile waves induce longitudinal strain on the ENS network; we rationalize this behavior by mechanical finite element modeling of the incompressible gut wall. We find that the longitudinal anisotropy of the ENS vanishes when contractile waves are suppressed in organ culture, showing that these contractile forces play a key role in sculpting the developing ENS. We conclude by summarizing different key events in the fetal development of the ENS and the role played by mechanics in the morphogenesis of this unique nerve network.